Effect of Au catalyst on the growth of the nanostructures prepared using VPT technique for enhanced biosensing performance of ZnO matrix - Neha Batra; Jatinder Pal Singh; Monika Tomar; Arijit Chowdhuri; Sonam Mahajan; Bilasini Devi Naorem (Chemical Physics Impact)
The current work investigates the influence of the Au catalyst layer on the development of ZnO nanostructures using the vapour liquid solid (VLS) modification of the vapour phase transport technique and their suitability as an efficient platform for detection of free cholesterol. ZnO nanostructures were prepared with and without the catalyst and subsequently, were characterized for structural, morphological, electrical and electrochemical properties. These ZnO nanostructures were deposited on platinum coated silicon (Pt/Si) to fabricate bioelectrodes forming ZnO/Pt/Si and ZnO/Au/Pt/Si configuration. The presence of catalyst was seen to considerably enhance the crystallinity, mobility, shape and morphology of the fabricated nanostructures. Most importantly, it was seen to enhance the electron transfer characteristics leading to a better electrochemical response. It was observed that the bioelectrode with Au as a catalyst layer leads to enhancement in sensitivity of ZnO nanostructures towards the detection of free cholesterol. The enhanced biosensing performance with sensitivity of 280 µAmM-1cm-1, linearity across a wide range from 0.12–12.93 mM of cholesterol and shelf life of 10 weeks is attributed to the presence of Au catalyst. Additionally, the study demonstrated that the Au-catalyzed ZnO nanostructures exhibit excellent reproducibility and stability, essential for practical biosensor applications.